Mindfulness-Based Islamic Digital Storybook for Early Childhood Emotional Regulation: Evidence from a Culturally Responsive SEL Intervention - Widyasari, Choiriyah; Hastuti, Isnaini Budi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Social-emotional learning in early childhood is often discussed through universal developmental frameworks, yet less attention has been given to how emotional regulation can be cultivated through digital media that are culturally and religiously meaningful for young children. This study examined the effectiveness of a mindfulness-based Islamic digital storybook in improving children’s basic emotional development and clarified how digital storytelling, mindful reflection, and Islamic moral narratives can work together as a culturally responsive SEL intervention. A quantitative quasi-experimental design with a pretest-posttest control group was used. Forty children aged 4–6 years from TK Alam Muhammadiyah Surya Mentari Surakarta, Indonesia, were selected purposively from two intact classes. The experimental group received four sessions of the mindfulness-based Islamic digital storybook intervention, while the control group continued conventional classroom learning. Data were collected using an expert-reviewed and pilot-tested basic emotional development instrument and analyzed using descriptive statistics, paired-sample t-tests, and ANCOVA. The experimental group’s mean score increased from 62.40 to 80.15, while the control group increased from 61.95 to 67.10. The experimental group showed significant improvement, t(19) = 9.12, p < .001, whereas the control group did not, t(19) = 2.01, p = .058. ANCOVA confirmed a significant group effect after controlling for pretest scores, F(1, 37) = 27.63, p < .001, partial η² = .421. These findings suggest that emotional recognition, expression, regulation, and empathy can be strengthened when digital stories are mediated through teacher guidance, mindfulness pauses, and familiar moral values. The study contributes a Digital, Mindful, and Moral Narrative approach, although wider samples and delayed posttests are needed in future studies.